2004
DOI: 10.4102/ojvr.v71i4.248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urea-molasses block supplementation on grazing weaner goats naturally infected with gastrointestinal nematodes

Abstract: <span>The influence of feeding urea-molasses blocks (UMB) on growth and gastrointestinal (GI) nematode parasitism of weaner goats grazing the same pasture was investigated on a farm in Nyandarua District, Kenya. Thirty female Small East African goat kids at an average age of 5 months were initially treated with albendazole orally (5 mg kg<sup>-1</sup> body mass) and randomly assigned into one of two groups: group I were fed UMB prepared using a cold process and group II kids (controls) receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Les blocs multinutritionnels constituent l'un des supports de cette supplémentation (Moujahed et al, 2003) et connaissent un succès croissant : ils ont été adoptés dans plus de 60 pays (Ben Salem et al, 2007). Au Kenya, la complémentation des caprins à base de bloc mélasse-urée a permis d'accroître le gmq de 83 g chez les animaux témoins à 151 g chez les animaux complétés (Waruiru et al, 2004). Le traitement de la paille à l'urée explore partiellement le même principe et constitue une autre voie d'augmentation de la productivité des animaux.…”
Section: Amélioration De La Santé Des Caprinsunclassified
“…Les blocs multinutritionnels constituent l'un des supports de cette supplémentation (Moujahed et al, 2003) et connaissent un succès croissant : ils ont été adoptés dans plus de 60 pays (Ben Salem et al, 2007). Au Kenya, la complémentation des caprins à base de bloc mélasse-urée a permis d'accroître le gmq de 83 g chez les animaux témoins à 151 g chez les animaux complétés (Waruiru et al, 2004). Le traitement de la paille à l'urée explore partiellement le même principe et constitue une autre voie d'augmentation de la productivité des animaux.…”
Section: Amélioration De La Santé Des Caprinsunclassified
“…As an example, exist the work of Gárate-Gallardo et al (2015) in this trial one group of animals was fed with 108g fresh basis of ground maize, and two more groups were fed with ground maize at 1% and 1.5% daily, and the control group remain without supplementation; it is found animals supplemented with 1.5% of body weight increased their daily weight gain in24% compared to animals infected a no supplemented, besides, there was a decrease in the fecal egg count by 55% and the partial budget shows better total gains and a net gain of 5.8 dollars per animal (Gárate-Gallardo et al, 2015). Similarly, it is reported that the use blocks of urea-molasses decrease the fecal egg count and help animals to withstand the detrimental effects of the parasite and getting gains plus 45% in treated animals (Waruiru et al, 2004).…”
Section: C) Use Of Nutritionmentioning
confidence: 86%
“…Mhomga et al, (2012) observed that there is a positive correlation between protein supplementation, weight gain and BCS in goats. In animals with moderate-heavy and undernourished infections, the higher the EPG, the greater the competition for nutrients, and in susceptible animals, the despoiling effect will result in evident clinical signs (Waruiru, Ngotho and Mutune, 2004), which will be re ected in a decrease in the good -being and expression of genetic, nutritional competence and, consequently, animal performance, whether for meat, milk and wool production (Charlier et al, 2020).…”
Section: Animal Performance and Endoparasitosismentioning
confidence: 99%